Students’ Perceptions Towards the Application of Gamification in English Class - Ariati, Shinta Dwi; Iswahyuni, Iswahyuni (ELLITE, 2023)
The integration of technology in education is rapidly increasing. Thus, academic practitioners are expected to utilize it optimally in teaching and learning process. One of the ways is to apply gamification in the classroom. This study aims to investigate the students' perception of the application of gamification in English classes. This research was conducted using a qualitative design and the data presented were descriptive through data interpretation. To answer the research questions, the researcher used semi-structured interviews in a face-to-face setting with 31 seventh-graders in one of the public junior high schools in Malang. The results of the study were to investigate students' perceptions of the application of gamification in learning English and students' insights about digital facilities in the school. The questions from interviews conducted covered several aspects, including (i) student interest in accessing digital games; (ii) student learning motivation; (iii) digital resource facilities and the ability of teachers to operate digital resources. The study found that more than half of the students in the class frequently accessed digital games and even had a favorite game. Students also gave a satisfactory perception regarding the application of gamification in the classroom because it can increase learning motivation. Students also gave their perceptions of the digital resource facilities at school and the teachers' ability to operate them.